(untitled) (ModaPalavra e-periódico, 2022)
The aim of this article is to analyze the news published about slow fashion on websites specialized in fashion journalism and identify how specialized journalism in/in fashion has been an important vector of information and ethical awareness about the responsible consumption in Western societies of the 21st century. To this do so, through basic, qualitative and descriptive research, a comparative content analysis of three blogs specialized in fashion was undertaken: (I) Fashion without crisis, (II) Modefica and (III) Urban Stylo, from news and reports on the slow fashion movement. The results showed that, although these websites mostly present fashion trends such as looks of the day and color cards dictated by bloggers, these reveal themselves as fruitful media spaces for more conscious approaches and sustainable alternatives in the fashion content presented.